Hepatoprotective action of Sonchus oleraceus against paracetamol-induced toxicity via Nrf2/KEAP-1/HO-1 pathway in relation to its metabolite fingerprint and in silico studies - Mohamed F. Abdelhameed; Marawan A. El-Baset; Amira R. Khattab; Rehab F. Taher; Mohamed A. El-Saied; Asmaa S. Abd Elkarim; Ahmed F. Essa; Ahmed A. El-Rashedy; Mohamed A. Farag; Hiroshi Imagawa; Abdelsamed I. Elshamy; Ahmed M. Abd-ElGawad (PLoS ONE, 2025)
Background Paracetamol overdose causes severe hepatotoxicity. Sonchus oleraceus is traditionally used to treat liver disorders, but its potential against paracetamol-induced liver injury is unexplored. This work aimed to investigate the protective mechanisms of an S. oleraceus extract (SOEtOH) using in vivo, histological and biochemical assessments along with metabolomics profiling and in silico studies, including molecular docking and dynamic simulations (MD). Methods and findings SOEtOH was administered to rats with paracetamol-induced hepatotoxicity at 50, 100, and 200 mg/kg doses. Serum enzymes, hepatic antioxidants, and histopathology were evaluated. UPLC-MS characterized bioactive metabolites and molecular docking and assessed their anti-inflammatory potential. SOEtOH significantly restored serum ALT and AST toward normal levels in a dose-dependent manner. It also replenished depleted hepatic glutathione (up to 3.9-fold) and superoxide dismutase (up to 4.7-fold). Immunohistochemistry revealed SOEtOH progressively attenuated caspase-3 expression related to apoptosis. It also ameliorated characteristic histopathological alterations like necrosis, inflammation, and sinusoidal congestion. Thirty-two bioactive metabolites, including flavonoids, phenolic acids, and terpenes, were identified. Molecular docking revealed potent anti-inflammatory effects via JNK inhibition, with luteolin-O-dihexoside, isorhamnetin-O-hexoside, di-O-caffeoylquinic, and kaempferol-O-hexoside having the strongest binding affinities. MD simulations demonstrated that these compounds’ complexes significantly contribute to JNK1 and JNK2’s catalytic binding site. Conclusion This integrated study demonstrates that SOEtOH protects against paracetamol hepatotoxicity by mitigating oxidative stress and inhibiting pro-inflammatory/apoptotic signaling. Our results reveal therapeutic lead compounds that may be further explored for clinical applications.